Performan Ternak Entog Di Pedesaan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan Sumatera Barat - Khalil Khalil; P.S. Yuspa (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The field suwey was carried out to identify the most critical factors that influence the performances of muscovy duck raised extensively under village condition in sub district Linggo Sari Baganti, Pesisir Selatan, West Sumatra. Thirty-three muscovy duck farmers, which were distributed in 4 villages in the sub district, were selected and intewiewed. Information collected included: flock size, egg production, egg hatchability, mortality, daily management practices, feed and feeding and health control. The average number of muscovy ducks raised was 11 ducks/farmer. The ducks laid egg 2-3 times per year with the average number of 12 eggs/duck/laying period. The hatchability of egg was about 84%, but the mortality of young duck during starter period was found very high, i.e. 42 %. Although about 67 % gave supplemented feed for their ducks, most of the feed consumed by the ducks were originated from scavenging. Most of farmers (70 %) did not take care young ducks. The ducklings were let to scavenge with their mother for about 12 weeks of old. Such feeding and management practices might be the major causing factors for the low egg production and high mortality of young duck.